2016
DOI: 10.1111/1346-8138.13679
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 derivatives, alone or in combination with glucocorticoids, suppress streptococcal pyrogenic enterotoxin A‐stimulated proliferation of peripheral blood mononuclear cells in patients with psoriasis

Abstract: Bacterial colonization on skin or tonsil may influence the clinical response of patients with psoriasis to immunosuppressive drugs. However, few studies have investigated the effects of bacterial superantigens on therapy in these patients. Recently, combination therapy with topical glucocorticoids (GC) and vitamin D3 (VD3) appears to be more effective than GC or VD3 monotherapy for psoriasis. We evaluated the suppressive effects of betamethasone butyrate propionate (BBP), three VD3 derivatives (calcipotriol, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In addition, the CCL20/CCR6 chemotactic system is critically involved in the maintenance of the TNF‐α/IL‐23/IL‐17A axis. Therapeutic agents for psoriasis include topical steroids, topical vitamin D3 derivatives, phototherapy, phosphodiesterase‐4 inhibitors, cyclosporine, methotrexate and biologics targeting TNF‐α, IL‐23 and IL‐17A . As the TNF‐α/IL‐23/IL‐17A axis plays a pivotal role in the pathogenesis of psoriasis, the efficacy of anti–TNF‐α/IL‐23/IL‐17A biologics is excellent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the CCL20/CCR6 chemotactic system is critically involved in the maintenance of the TNF‐α/IL‐23/IL‐17A axis. Therapeutic agents for psoriasis include topical steroids, topical vitamin D3 derivatives, phototherapy, phosphodiesterase‐4 inhibitors, cyclosporine, methotrexate and biologics targeting TNF‐α, IL‐23 and IL‐17A . As the TNF‐α/IL‐23/IL‐17A axis plays a pivotal role in the pathogenesis of psoriasis, the efficacy of anti–TNF‐α/IL‐23/IL‐17A biologics is excellent …”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic agents for psoriasis include topical steroids, topical vitamin D3 derivatives, phototherapy, phosphodiesterase-4 inhibitors, cyclosporine, methotrexate and biologics targeting TNF-α, IL-23 and IL-17A. [38][39][40][41][42][43][44][45][46] As the TNF-α/IL-23/IL-17A axis plays a pivotal role in the pathogenesis of psoriasis, the efficacy of anti-TNF-α/IL-23/IL-17A biologics is excellent. 3,24,46 In this review, we will summarize the current research topics regarding the CCL20/CCR6 axis in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated TNF‐ α /IL‐23/IL‐17 axis coincides with the characteristic histopathology of psoriasis, such as epidermal hyperproliferation, aberrant differentiation and neutrophilic microabscess. Regarding treatments, topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation . Systemic treatments, such as cyclosporine, methotrexate and the phosphodiesterase 4 inhibitor apremilast, are useful for patients with extensive lesions .…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%
“…Regarding treatments, topical application of steroids and vitamin D3 analogues inhibits psoriatic inflammation and normalizes epidermal differentiation. [61][62][63][64][65] Systemic treatments, such as cyclosporine, methotrexate and the phosphodiesterase 4 inhibitor apremilast, are useful for patients with extensive lesions. [66][67][68] Clinical trials have demonstrated the efficacy of the oral janus kinase inhibitor tofacitinib for psoriasis.…”
Section: Current Pathogenesis Of Psoriasis and Its Treatmentsmentioning
confidence: 99%
“…[6][7][8][9][10] Therapeutic modalities for psoriasis include topical steroids, topical vitamin D3 derivatives, phototherapy, phosphodiesterase-4 inhibitors, cyclosporine, methotrexate, and biologics targeting TNF-a, IL-23, and IL-17A. [11][12][13][14][15][16][17][18][19] The excellent therapeutic efficacy of anti-TNF-a/IL-23/IL-17A biologics for psoriasis point to a central role of the TNF-a/IL-23/IL-17A axis in its pathogenesis. 20,21 Additionally, genetic and environmental factors are known to be involved in its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%